Association between Drug-Related Problems and Blood Pressure of Hypertensive Patients Admitted to Universitas Sumatera Utara Hospital - Mutiara Siahaan; Azizah Nasution; Wiryanto Wiryanto; Iksen Iksen (Borneo Journal of Pharmacy, 2023)
Patients with hypertension usually experience chronic comorbidities and complications that require complex treatment (polypharmacy), which can further cause drug-related problems (DRPs) and interfere with the required clinical outcomes. This study, by using a case-control prospective cross-sectional, aimed to analyze the association between DRPs and blood pressures (BPs) of hypertensive patients admitted to Universitas Sumatera Utara (USU) hospital from July to September 2021. The incidence of DRPs was analyzed and classified according to the Cipolle classification system and reliable literature. Blood pressures of the patients were classified into controlled and uncontrolled BPs. The association between DRPs and BP was analyzed using the Chi-Square test. Most of the patients (57.5%) were female. Their mean age was 59±9.94 (years). The mean incidence of DRPs experienced by the patients was 1.78±0.79. The most frequently occurred DRPs were drug interactions. There was a significant association between the number of DRPs experienced by the patients and their BPs (p=0.02). DRPs are the contributing factor to the uncontrolled BPs of hypertensive patients.